Preventive and responsive plans to COVID-19 epidemic in a leading teaching hospital in Milan, Italy. (30th September 2020) - Bellini, L; Bossi, E; Bucci, D; Capraro, M; Chiappa, F; Ambrosio, A
Abstract: Issue: Following the SARS-Cov-2 outbreak in Wuhan, China, the first case of COVID-19 was reported in Codogno, Lombardy, Italy, on 20 February 2020. The ongoing epidemic has exposed the health care system to a severe stress. San Raffaele Hospital (OSR) in Milan, Italy - a leader in the emergency management, may provide a benchmarking experience useful for other countries. Description of the Problem: OSR has established a task force including the health care director, the Infections Prevention and Control Committee (IPCC) and the head of ward and outpatients' facilities management area in order to assess the situation and to define a multi-step strategy. The management process has been divided in two steps. Firstly, a preventive phase was devised, in a preparedness perspective, to avoid the spread of the infection to the Healthcare Professionals (HCP). Secondly, a reorganizational phase was implemented to guarantee assistance to infected patients, especially the critical ones. Results: Before the outbreak, the IPCC updated OSR's procedures, based on the WHO's, national and regional guidance, planned a lectures series and an online survey to train healthcare professionals and proposed to stack Personal Protective Equipment (PPE) to face the expected shortage. The Head of the facilities management area defined separate pathways in the Emergency Department in order to isolate patients with respiratory symptoms, set up a new ward, with 26 beds and dedicated personnel, as well as two Intensive Care Units, with 13 beds, Some wards were merged and more healthcare workers were moved to the COVID-19 units. Lessons: The coordination between task force members has been crucial for translating the multi-step strategy in a quick reorganization of the whole hospital. Despite early preparations, we could not anticipate the evolution of the outbreak and its logistic impact, especially on the PPE procurement. Key messages: A major Hospital was proved to be capable to respond to the changing healthcare requests. Organizational flexibility is crucial for proper emergency management.